Purinergic signaling and gene expression of purinoceptors in the head kidney of the silver catfish Rhamdia quelen experimentally infected by Flavobacterium columnare - Baldissera M.D. (2020)
© 2020 Elsevier LtdThe head kidney is a lymphoid immune organ that plays a key role in the immune and inflammatory responses of teleost fish. It is associated with immunoglobulin G production and differentiation of B cells. The presence of a multi-enzymatic complex found anchored in the plasma membrane makes the head kidney an important purinergic-dependent tissue. Purinergic signaling has been associated with these responses under pathological conditions via regulation of extracellular adenosine triphosphate (ATP), the main damage molecular associated pattern agent released during bacterial infections. The aim of this study was to determine whether purinergic signaling is a pathway associated with impairment of immune responses in silver catfish (Rhamdia quelen) experimentally infected by Flavobacterium columnare, as well as to evaluate the role of P2 purine receptors in this response. Triphosphate diphosphohydrolase (NTPDase) activity in the head kidney was significantly lower in silver catfish experimentally-infected F. columnare 72 h post-infection (hpi) than in the control group, while no significant difference was observed with respect NTPDase activity on adenosine diphosphate, as well as on 5′-nucleotidase and adenosine deaminase activities. Extracellular ATP levels were significantly higher in the head kidney of experimentally-infected fish than in the control group at 72 hpi. Finally, p2ry11 and p2rx3 purine receptor levels were significantly higher in experimentally-infected fish than in the control group at 72 hpi. We conclude that purinergic signaling in the head kidney of silver catfish infected by F. columnare creates a pro-inflammatory profile that may contribute to impairment of immune and inflammatory responses via reduction of ATP hydrolysis and its accumulation in the extracellular milieu, accompanied by upregulation of p2ry11 and p2rx3 purine receptors, leading to pro-inflammatory status.